Estimation of Blood Glucose Levels And Hemodynamic Changes During Laparoscopic Cholecystectomy: A Comparison of Dexmedetomidine and Nalbuphine - Fayaz, Fakher-e-; Asad, Naila; Khurshid, Hana; Butt, Zulqarnain; Awan, Nazir; Saeed, Aisha (Pakistan Armed Forces Medical Journal, 2022)
Objective: To compare the effect of Dexmedetomidine and Nalbuphine premedication on changes in hemodynamics and neuroendocrine stress response under general anaesthesia by analyzing the variation of perioperative serial blood glucose levels. Study Design: Prospective comparative study. Place and Duration of Study: Services Hospital, Lahore Pakistan, from Oct to Dec 2020. Methodology: Total 90 patients aged between 30-and 65 years were allocated randomly into three groups. Group-D patients (n=30) were administered Dexmedetomidine 0.5 μg/kg in 100 ml normal saline, group-N (n=30) were given Nalbuphine 0.1 mg/kg in 100ml saline, and group-S received saline (100ml) throughout 15 minutes before induction of anaesthesia for laparoscopic cholecystectomy. General Anaesthesia was administered. Intra-abdominal pressure was maintained after abdominal insufflation with carbon dioxide between 12-15 mmHg. Blood glucose levels were analyzed preoperatively, 30 minutes after the beginning of surgery, at extubation and 2.5 hours postoperatively. Hemodynamic changes were recorded after premedication, 15 and 30 minutes after pneumoperitoneum and extubation. Results: Random mean blood sugar levels were 135.23 mg/dl with Dexmedetomidine and 123.33 mg/dl with Nalbuphine and 122.53 mg/dl in saline group (p<0.05). There was a greater decrease in hemodynamic parameters with group-D than with groups N and S (p<0.01). Conclusion: During laparoscopic cholecystectomy, intravenous Dexmedetomidine premedication attenuates the hemodynamic stress response better than Nalbuphine but does not suppress the neuroendocrine response as estimated by a rise in random blood glucose level.